This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Radial geodesics in Schwarzschild spacetime Spherically symmetric solutions to the Einstein equation take the form ds 2 = 1 + a r dt 2 + dr 2 1 + a r + r 2 dθ 2 + r 2 sin 2 θdϕ 2 where a is constant. We also have the connection components, which now take the form (using e ν = e λ = 1+ a r , and therefore ν = ln ( 1 + a r ) and ν , 1 = a r 2 e ν Γ 00 = 0 Γ 01 = Γ 10 = a 2 r 2 ( 1 + a r ) Γ 1 00 = 1 2 1 + a r a r 2 Γ 1 11 = a 2 r 2 ( 1 + a r ) Γ 1 01 = Γ 1 10 = 0 Γ 11 = 0 Γ 2 12 = Γ 2 21 = 1 r Γ 1 22 = r 1 + a r Γ 3 13 = Γ 3 31 = 1 r Γ 1 33 = 1 + a r r sin 2 θ Γ 3 23 = Γ 3 32 = cos θ sin θ Γ 2 33 = sin θ cos θ Now consider the geodesic equation for a particle which starts from rest at time τ = t = 0 . 0 = du a dτ + Γ a bc u b u c It might seem that the initial velocity 4vector is u a = (1 , , , 0) , but this is not allowed. Using the line element, ds 2 = dτ 2 , we must have 1 = 1 + a r dt dτ 2 + 1 c 2 ( 1 + a r ) dr dτ 2 + r 2 c 2 dθ dτ 2 + r 2 c 2 sin 2 θ dϕ dτ 2 where c is the speed of light. If there is no initial motion in the spatial directions we must have u = dt dτ = 1 q 1 + a r where r is the initial radial position. The geodesic equation for each component is then (at the initial time), 0 = 1 c du dτ + 2Γ 01 u u 1 1 0 = 1 c du 1 dτ + Γ 1 00 u u + Γ 1 11 u 1 u 1 + Γ 1 22 u 2 u 2 + Γ 1 33 u 3 u 3 0 = 1 c du 2 dτ + 2Γ 2 21 u 2 u 1 + Γ 2 33 u 3 u 3 0 = 1 c du 3 dτ + 2Γ 3 13 u 1 u 3 + Γ 3 23 u 2 u 3 Notice that if u 2 = 0 or u 3 = 0 then the corresponding accelerations also vanish, so they remain zero. However, u 1 cannot remain zero. For radial motion, substituting for the connection coefficients, we therefore have 0 = 1 c du dτ a r 2 ( 1 + a r ) u u 1 0 = 1 c du 1 dτ 1 + a r a 2 r 2 u u + a 2 r 2 ( 1 + a r ) u 1 u 1 We also have the relation given by the line element, 1 = 1 + a r dt dτ 2 + 1 1 + a r 1 c dr dτ 2 First equation Integrate the first equation, 0 = du u adr r 2 ( 1 + a r ) = ln u ˆ adr r ( r + a ) = ln u ˆ 1 r 1 r + a dr = ln u ln r + ln( r + a ) ln b for some constant b, and therefore 1 + a r u = b Evaluating at the initial condition, we see that b = q 1 + a r . Radial component of velocity from the line element Now substitute into the line element equation to find u 1 , 1 = 1 + a r ( u ) 2 + 1 1 + a r ( u 1 ) 2 1 = 1 + a r b 1 + a r 2 + 1 1 + a r ( u 1 ) 2 ( u 1 ) 2 = b 2 1 + a r u 1 = r b 2 1 + a r = r a r a r 2 Now integrate to find r ( τ ) , cτ = ˆ dr q a r a r = 1 √ a ˆ √ rdr q r r 1 Let y = √ r . Then dy = 1 2 dr √ r , so cτ = 2 √ a ˆ y 2 dy q y 2 r 1 Now let y = √ r cosh ξ...
View
Full
Document
This note was uploaded on 05/28/2011 for the course MATH 2 taught by Professor Fred during the Spring '11 term at Foothill College.
 Spring '11
 Fred

Click to edit the document details